A simple 2, 6-diphenylpyridine-based fluorescence "turn-on" chemosensor for Ag+ with a high luminescence quantum yield. (June 2017) - Zhang, Yuan; Wang, Dehui; Sun, Changliang; Feng, Huiyan; Zhao, Dezhi; Bi, Yanfeng
Abstract: A sensitive and simple 2, 6-diphenylpyridine-based receptor servered as a "turn-on" fluorescent chemosensor was designed and synthesized for selectively sensing Ag + ions in aqueous media with an anomalously quantum yield. The probe exhibits high selectivity toward Ag + over other common metal ions, displaying a significant fluorescent turn on nature in the presence of Ag + . The fluorescence response is explained by X-ray diffraction analysis, mass spectrometry, and theoretical calculations. The unprecedentedly high luminescence quantum yield can be attributed to intraligand charge transfer (ILCT) transitions with mixed some Ag(I) 5p orbitals perturbation characters. Finally, the results of cell experiments show that the probe can be used to selectively detect Ag + in mammalian cells. Graphical abstract: A simple 2, 6-diphenylpyridine (CˆNˆC)-based cyclometalated receptor as "turn-on" fluorescent probe was designed and synthesized for selectively sensing Ag + with an unprecedented quantum yield in living cells. Highlights: CNC-OMe was one of the brightest Ag + -binding chemosensors with high selectivity and sensitivity to date. The sensing mechanism is proposed on the basis of the experimental and theoretical studies. CNC-OMe could act as efficient sensing probe for the detection of Ag + in living cells.